Resource limitations and teacher training challenges in implementing the steam-based merdeka curriculum for kindergarten's cognitive and creative development - Sunanih, Sunanih; Maulidah, Neni; Sunhaji , Sunhaji; Mutijah , Mutijah (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
This study explores the implementation of the STEAM-based Merdeka Curriculum in Kindergarten learning and its impact on children's cognitive and creative development in West Java. A survey method collected both qualitative and quantitative data from 44 kindergarten teachers in West Java, using open and closed-ended questionnaires analyzed through descriptive techniques. Results show a significant positive impact, particularly enhancing children's critical thinking and creativity. Respondents noted increased engagement and enthusiasm in learning, with 36.4% emphasizing improved critical thinking and 31.8% noting increased creativity. However, challenges included the need for advanced teacher training (38.6% of respondents) and meticulous planning, along with resource limitations (40.9% of respondents) and facility constraints. In kindergarten settings, STEAM elements—Science, Technology, Engineering, Arts, and Mathematics—were integrated through various creative approaches such as experiments (e.g., inflating balloons with soda), art projects (e.g., making letter cards), and project activities (e.g., growing mung bean sprouts). Additionally, the use of digital devices like laptops and projectors, as well as educational games, were employed. These methods provided a comprehensive and engaging learning experience, enhancing children's cognitive skills and creativity. This study highlights the crucial role of local context and the need for comprehensive support to successfully implement the curriculum. With appropriate support, the curriculum has great potential to improve early childhood education in Indonesia, aiding policy development and educational innovation.